Incorporating financial literacy in video clips amongst high school students - Khoo Yin Yin; Eng Tek Ong; Fatimah Salwa Abd. Hadi (Institute of Advanced Engineering and Science, 2024)
Young adults with enough financial knowledge can commonly make good financial decisions, whereas those who lack financial literacy are always burdened by student loans and credit card debts. Acquiring adequate financial knowledge has become crucial among young adults. The present study investigated the effectiveness of incorporating financial literacy into videos among high school students. The video clips were incorporated into financial literacy in the economics curriculum to engage students and facilitate their learning of financial literacy. This study employed the mixed-methods explanatory design. The data analysis procedures in this design involved collecting the quantitative data, analyzing the data, and using the data to guide the follow-up interviews. A total of 327 students participated in this study. The results showed a significant change in students’ behavior regarding financial literacy (F=271.847, p<.05). Financial literacy should be instilled to students from primary school through tertiary education to ensure long-term sustainability effects.